Description of a new species of Onychostenhelia Ito (Copepoda, Harpacticoida, Miraciidae) from the Bohai Sea, China - Huys, Rony; Mu, Fang-Hong (Zootaxa, 2008)
Onychostenhelia bispinosa sp. nov. is described from material collected from the Bohai Sea, China. It differs from the type and only known species of Onychostenhelia in the setal formula of the swimming legs, the form of the setae on the baseoendopod of P5 in both sexes, the female rostrum, the structure of the sexually dimorphic P4 exopod in the male, and size. Onychostenhelia, Cladorostrata and Delavalia belong to a core group within the Stenheliinae that exhibits an unusual morphology in the maxillule, the exopod and endopod being confluent at base but not actually fused to the supporting basis. Based on this circumstantial evidence it is postulated that in biramous limb patterning both exopodal and endopodal primordia are recruited from a common precursor and, consequently, patterns of axial diversification in crustacean limbs and the mechanisms of segmentation that establish them may have to be reinterpreted. Previously published evidence supporting the monophyly of the Stenheliinae is reviewed and a dichotomous key to the nine genera of the subfamily Stenheliinae provided.